Buyat Case: An Advocacy Against the Giant PT. International Newmont - Nur Isdah Idris (WANUA : Jurnal Hubungan Internasional, 2015)
AbstractOne key of the successful advocacy is a good networking amongst advocates. Bell and Delaney has shaped the important of networking by building coalition using diversities emerged from the community to be collaborated. Buyat case is one of the successful advocacy for marginalize people in Buyat pante village through some disputes with the giant gold miner, PT Newmont Minahasa Raya. This study case will show the significant coalitions amongst academicians, NGO workers, Government, researchers, and medias had succeed to advocate Buyat community in the same objectives which getting the community’s rights back and protecting the environment from further destruction of mining process.